Literackość w żydowskich i nie-żydowskich czeskich i polskich tekstach byłych więźniów obozu koncentracyjnego Auschwitz - Gardia, Magdalena (Univerzita Palackého v Olomouci, 2024)
The subject of the monograph is the camp texts of former prisoners of the Auschwitz concentration camp, of Jewish and non-Jewish origin, direct witnesses of the events, originally written in Czech or Polish. This work consists of two parts: theoretical and analytical.
Keywords: Literární věda